Pengaruh Tingkat Pengangguran, Tingkat Pendidikan Dan Laju Pertumbuhan Penduduk Terhadap Tingkat Kemiskinan Penduduk Provinsi Lampung Tahun 2013-2022 - Eka Fatimah; Evilia Gunawan; Iqbal Hasyim; Muhammad Kurniawan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research aims to determine and analyze the influence of the unemployment rate, education level and population growth rate on the poverty rate in Lampung Province in 2013-2022. The method used is a quantitative method with a descriptive and verification approach, with the data collection method in this research using time series data for 10 years, namely 2013-2022 from the total of Lampung Province, the data source is secondary data taken from the Agency The Lampung Provincial Statistics Center was analyzed using the classic assumption test, multiple linear regression test, and coefficient of determination using the Eviews application. Based on the results of calculations both partially and simultaneously, the unemployment rate, education level and population growth rate influence the poverty level of the population of Lampung Province in 2013-2022, with a coefficient of determination of 0.740, meaning that 74% of the poverty variable can be influenced by the unemployment rate, education level and population growth rate , while the remaining 26% can be explained by other variables which were not examined by researchers in this study. The suggestion that the government should make is to pay attention to improving the quality of human resources, by providing training to improve the education and skills of the workforce so that they can compete in getting jobs so that they are not trapped in poverty and suppressing the rate of population growth, for example by reviving the transmigration program, equal distribution. employment opportunities, imposing high tariffs on immigrants and so on.